OPTIMALISASI PEMUNGUTAN RETRIBUSI PELAYANAN KEBERSIHAN DI KOTA PEKANBARU - Rina Novi Safitri; Zulkarnaini Zulkarnaini (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aims to determine the extent to which the waste service retribution in Pekanbaru City runs optimally and the inhibiting factors it faces. Looking at the waste service retribution data for Pekanbaru City from 2017 to 2020, although it increases every year, the realization does not reach the predetermined target, therefore, it is necessary to optimize the waste service retribution in Pekanbaru City so that the realization of the waste service retribution is in accordance with the target set has been established. The optimization is carried out by looking at the collection of potential retribution data, its supervision, coordination and strategies for collecting retribution for waste services in Pekanbaru City. In addition, it must also pay attention to the number of retribution-collecting personnel, coordination between officers, the skills of officers and the role of the community in retribution for waste services. The theoretical concept used in this research is the optimization of retribution collection from Andriani in 2001. The research method used is qualitative with data collection techniques through interviews, observation and documentation. The results of this study are that there is still a need for optimal retribution for waste services in Pekanbaru City with the limited physical ability and skills of retribution collectors in collecting data and collecting retribution, and the role of the community is still lacking due to lack of coordination between garbage collectors and garbage retribution collectors. Of course, it is very influential on the realization of the waste service retribution in Pekanbaru City.